Factors fostering vocational students' workplace learning success in the real workplace environment - Nisula, Anna-Maija [Verfasser]; Metso, Sari [Verfasser] (My University, 2019)
"The present paper proposes a conceptual model in which both personal and perceived workplace-related factors affect vocational students' workplace learning success in real workplace environments, with workplace learning success constituted by students' professional learning and satisfaction. We empirically tested the proposed model in two survey datasets (N = 242 and N = 88) collected from Finnish final-year vocational students and their workplace instructors using structural equation modelling (SEM) based on partial least squares (PLS). The results show that supportive climate, interpersonal trust in the workplace, and students' self-efficacy all have a significant and positive impact on vocational students' subjective workplace learning success. The results differ based on whether the professional learning is evaluated subjectively by the student or objectively by the workplace instructor. We discuss the implications of the findings for theory and practice." (authors' abstract; BIBB-Doku)
Keywords: P 2.3 Auszubildende; I 2.2.1 Westeuropa; Auszubildender; Lernerfolg; Einflussfaktor; Arbeitsumwelt; Lernklima; Selbstwirksamkeit; Lernzielorientierung; Finnland